2017
DOI: 10.1080/03601234.2016.1270682
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mycotoxins in wheat grains exposed to fungicides on fusarium head blight control in southern Brazil

Abstract: Mycotoxins occurrence in wheat grains impose risks to human and animal health. The southern Brazil has favorable weather conditions for Fusarium graminearum infections and consequently for mycotoxins accumulation on grains. The goal of this study was to evaluate the behavior of new wheat commercial genotypes to Fusarium Head Blight (FHB), to control performance of new fungicide formulations and their relationship with mycotoxins concentration in grains. The manly mycotoxin occurrence on wheat grains in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The efficacy of some molecules belonging to SDHIs against other Fusarium species has been demonstrated in China, where F. asiaticum (a member of F. graminearum species complex [47]) strains were sensitive to the novel SDHI pydiflumetofen [48]. Moreover, in Southern Brazil, SDHIs in mixture with quinone outside inhibitors fungicides (QoI) were able to reduce F. graminearum on wheat in field conditions [49].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of some molecules belonging to SDHIs against other Fusarium species has been demonstrated in China, where F. asiaticum (a member of F. graminearum species complex [47]) strains were sensitive to the novel SDHI pydiflumetofen [48]. Moreover, in Southern Brazil, SDHIs in mixture with quinone outside inhibitors fungicides (QoI) were able to reduce F. graminearum on wheat in field conditions [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the field, prothioconazole is usually applied in combination with other active ingredients to obtain a higher FHB control. In fact, the combination with tebuconazole is very frequent and it showed a high efficacy on FHB, 23,60 and in particular towards F. graminearum 61,62 …”
Section: Discussionmentioning
confidence: 99%
“…A further, comprehensive study reported that tebuconazole + prothioconazole (TEBU+PROT; Prosaro) and metconazole (METC; Caramba) were the two most effective fungicides against FHB and DON if applied within a short period (up to 1 week) after anthesis (D'Angelo et al ., ). Under in vitro conditions, F. graminearum ascospore infection was most efficiently protected by prothioconazole (Marques et al ., ), followed by metconazole and tebuconazole (Klix et al ., ). According to Cromey et al .…”
Section: Chemical Management Strategiesmentioning
confidence: 99%